Analisis Perbandingan Algoritma Klasifikasi Data Mining Untuk Penentuan Bibit Unggul - Sugito, Bambang; Iqbal, Muhammad (Building of Informatics, Technology and Science (BITS), 2024)
Cocoa is one of the leading commodity crops from the growing plantation sub-sector, mostly cultivated by farmers in the form of community plantations. Cultivation is carried out so that it can continue to produce seeds and trees independently for the sustainability of the commodity. The process currently carried out in the selection of superior seeds is carried out by staff who are specifically assigned to that section. The process of selecting superior cocoa plant seeds should have been recorded and stored. Data mining is a process that uses statistical techniques, mathematics, artificial intelligence, and machine learning to extract and identify useful information and related knowledge from various large databases. Based on this problem, the C5.0 and K-Nearest Neighbor algorithms are applied to carry out the comparison process in predicting the need for superior seeds to be used. It will be able to provide accurate information and can be used as a consideration in the stock of superior cocoa seed needs. The process using the C5.0 and K-Nearest Neighbor algorithms has been successfully carried out, from the testing process carried out that the C5.0 algorithm has a better performance result of 87.50% compared to the K-Nearest Neighbor algorithm of 62.50%.